2017
DOI: 10.1073/pnas.1619442114
|View full text |Cite
|
Sign up to set email alerts
|

Maturation arrest in early postnatal sensory receptors by deletion of the miR-183/96/182 cluster in mouse

Abstract: The polycistronic miR-183/96/182 cluster is preferentially and abundantly expressed in terminally differentiating sensory epithelia. To clarify its roles in the terminal differentiation of sensory receptors in vivo, we deleted the entire gene cluster in mouse germline through homologous recombination. The miR-183/96/ 182 null mice display impairment of the visual, auditory, vestibular, and olfactory systems, attributable to profound defects in sensory receptor terminal differentiation. Maturation of sensory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 50 publications
4
70
1
Order By: Relevance
“…Expectedly, AGO2-loaded miRNA found in both DR and PD groups, comprised miRNAs that are known to play a role in retinal development and homeostasis such as the photoreceptor cluster miR-183/96/182 (Bellon et al, 2017, Busskamp et al, 2014, Fan et al, 2017, Karali et al, 2007, Krol et al, 2010, Lumayag et al, 2013, Xiang et al, 2017, Xu et al, 2007; miR-204-5p (Barbato et al, 2017, Conte et al, 2010, Conte et al, 2015, Karali et al, 2016, let-7a-5p (La Torre et al, 2013) and miR-124-3p (Chu-Tan et al, 2018, Karali et al, 2007, Sanuki et al, 2011, showing consistent overlap with previous studies. However, despite significant changes in differential global miRNA expression in the damaged retina, there were no significant changes in AGO2-loaded miRNA between DR and PD retinas suggesting that the retina appears to be utilising the existing miRNA population in both physiological states.…”
Section: Discussionsupporting
confidence: 86%
“…Expectedly, AGO2-loaded miRNA found in both DR and PD groups, comprised miRNAs that are known to play a role in retinal development and homeostasis such as the photoreceptor cluster miR-183/96/182 (Bellon et al, 2017, Busskamp et al, 2014, Fan et al, 2017, Karali et al, 2007, Krol et al, 2010, Lumayag et al, 2013, Xiang et al, 2017, Xu et al, 2007; miR-204-5p (Barbato et al, 2017, Conte et al, 2010, Conte et al, 2015, Karali et al, 2016, let-7a-5p (La Torre et al, 2013) and miR-124-3p (Chu-Tan et al, 2018, Karali et al, 2007, Sanuki et al, 2011, showing consistent overlap with previous studies. However, despite significant changes in differential global miRNA expression in the damaged retina, there were no significant changes in AGO2-loaded miRNA between DR and PD retinas suggesting that the retina appears to be utilising the existing miRNA population in both physiological states.…”
Section: Discussionsupporting
confidence: 86%
“…We can make some further assumptions about the role of miR-1271-5p in the brain by looking at the activity of its seed pairing homolog miR-96-5p, as it is likely they have similar targets and regulatory activity [15]. For example, miR-96-5p expression has been associated with the coordination of neural crest [49] and auditory hindbrain development [50], as well as the induction and progression of neuronal differentiation [51][52][53]. It has also been shown to be involved in the regulation of long-term memory [54,55] and pain sensitivity [56].…”
Section: Discussionmentioning
confidence: 99%
“…It was originally identified as a sensory organ-specific miRNA cluster [7, 8]. We and others have shown that miR-183/96/182 is required for the normal function of all major sensory organs, including vision [8], hearing and balance [8-10], olfaction [11], and pain [12]. Recently, mounting evidence from our group and others demonstrated that member(s) of miR-183/96/182 are also expressed and play important roles in both innate [13-16] and adaptive immune systems [17-19], suggesting that miR-183/96/182 provides one of the first shared genetic links between the immune and traditional sensory systems, supporting the recently emerging concept of the immune system as a sensory system [20].…”
Section: Introductionmentioning
confidence: 99%